Phytochemical composition of Anastatica hierochuntica L., can it fight the toxigenic bacterial agents responsible for food poisoning? (Microbes and Health, 2017)
The present work aims to study the biological activity of Anastatica hierochuntica L., against four bacterial strains considered as toxigenic responsible for food-borne infection. The plant was collected from Tindouf region (Far Southwest of Algeria). In this study we performed a phytochemical screening and evaluation of antibacterial activity of three macerates of two vegetative parts (seeds and stems) by two methods (disk and wells diffusion method). The yield of aqueous, methanolic and etheric macerates of the seeds and stems were (5.1; 3.8), (5; 1.4) and (2; 0.95)% respectively. Also, it appears that macerates obtained were rich in bioactive phyto-constituents particularly the seed of the plant. They showed the presence of ten large chemical groups. The antibiotic resistance profile of the bacterial strains tested showed an increased resistance to several families of antibiotics. The evaluation of the antibacterial activity of the extracts showed that methanolic and aqueous macerates of the seed were more active against Gram positive bacteria. The methanolic macerate of the stems was less active. However, other macerates were ineffective. The results obtained show that the plant has an average antibacterial activity and that depends on extract concentration used.Microbes and Health, June 2017, 6(1): 5-8